Inspecting evidence between cancer therapy-induced oral mucositis and periodontitis: A narrative review - Novaes, Cristina De Paula; Moreira, Aline; Chaves, Maria Das Graças Afonso Miranda; Fabri, Gisele Maria Campos (European Journal of General Dentistry, 2019)
This narrative review aims to update the reader about the current issues surrounding central aspects implicated in the relationship between oral mucositis (OM) and periodontitis. We searched Medline/PubMed database. English language publications were included in the study. Paired reviewers selected articles for inclusion and extracted data. Forty-four studies met our inclusion criteria. The majority of the studies were review (63.8%) and clinical studies (36.2%). There is a lack of studies regarding the association of periodontal disease (PD) and OM. However, there are pathogenic similarities between them. Look for scientific evidence to confirm the relationship between PD and OM is imperative. Thus, if periodontitis can actually interfere with the occurrence and severity of OM, the establishment of strategies to reduce it may contribute to better control of OM, a serious adverse effect of cancer treatment.
Keywords: Cancer therapy; oral mucositis; periodontitis